Analysis of Initial Deployment Strategy for Low-Orbit Large-Scale Constellations. (8th November 2022) - Li, Feifei; Hu, Min; Che, Bin; Yang, Huaibin; Cheng, Yuancang
Abstract : With the development of commercial space technology, low-orbit large-scale satellite constellation has shown great development potential in communication services and military applications due to its advantages of low delay, strong signal, high coverage rate, fast communication rate, and low cost of mass production. It has become an urgent problem in the field of satellite constellations to study the perturbation evolution law of low-orbit large-scale constellation initialization and orbit maintenance, and how to maintain and control the deployment and initialization of low-orbit satellite constellations efficiently, economically, and stably. In this paper, the satellite motion law, constellation configuration evolution characteristics, and constellation initialization control strategy are analyzed considering the perturbation of earth's nonspherical gravity and atmospheric drag under the orbit deviation of satellite orbit elements. Firstly, MonteCarlo simulation was used to simulate the deviation of satellite initial orbit elements, and the evolution law of ascending ascension point and phase angle of different constellations was analyzed and, secondly, establish the initialization phase constellation deployment and the ascending node right ascension deployment of mathematical equations, using Starlink constellation (V1.0-L3, 8) satellite TLE data; initialization of Leo constellation orbit plane is analyzed, by considering the orbit bias satellite simulation data; the same orbital plane satellite initialization phase deployment method is analyzed; finally, this paper provides some suggestions for the future deployment and maintenance control strategy of low-orbit constellation.